A comparative study of microneedling combined with topical 5-fluorouracil versus microneedling alone in treatment of localized stable vitiligo - Shaiphali Chhabra; Yatendra S Chahar; Akanksha Singh (Wolters Kluwer Medknow Publications, 2021)
Context: Vitiligo is an acquired pigmentary disorder of the skin that is characterized by circumscribed, depigmented macules, and patches. Aims: To compare the therapeutic efficacy and safety of microneedling combined with topical 5-fluorouracil solution versus microneedling alone on stable patches of vitiligo. Settings and Design: Hospital-based interventional prospective study. Methods and Material: We selected 46 patients in the age group of 10-50 years having patch stability of at least 1-year duration. The patients were randomly assigned into two groups of 23 patients each. Group A was treated with microneedling followed by application of 5-fluorouracil which was available in the form of a solution (50 mg/mL) whereas Group B was treated with microneedling alone. The procedure was repeated after every 15 days up to 4 months and patient follow-up along with the grading of repigmentation was done till 6 months. The side effects were noted. Statistical Analysis Used: Statistical Package for Social Sciences (SPSS) software, version 25.0. The results were analyzed using the Chi-square test and t-test and P < 0.05 was considered significant. Results: At the end of 6 months, excellent response (>75% repigmentation) was reported in 35 patches (48.6%) in Group A treated with microneedling combined with 5-fluorouracil whereas only 12 patches (16.9%) showed an excellent response in Group B treated with microneedling alone. Conclusions: Combining microneedling with 5-fluorouracil is a simple, safe, well tolerable, and effective modality than microneedling alone for treating small localized vitiligo patches.